Controlling the Physical Behavior and Biological Performance of Liposome Formulations Through Use of Surface Grafted Poly(ethylene Glycol). Issue 2 (April 2002) - Allen, C.; Dos Santos, N.; Gallagher, R.; Chiu, G.N.C.; Shu, Y.; Li, W.M.; Johnstone, S.A.; Janoff, A.S.; Mayer, L.D.; Webb, M.S.; Bally, M.B.
Abstract : The presence of poly(ethylene glycol) (PEG) at the surface of a liposomal carrier has been clearly shown to extend the circulation lifetime of the vehicle. To this point, the extended circulation lifetime that the polymer affords has been attributed to the reduction or prevention of protein adsorption. However, there is little evidence that the presence of PEG at the surface of a vehicle actually reduces total serum protein binding. In this review we examine all aspects of PEG in order to gain a better understanding of how the polymer fulfills its biological role. The physical and chemical properties of the polymer are explored and compared to properties of other hydrophilic polymers. An evidence based assessment of several in vitro protein binding studies as well as in vivo pharmacokinetics studies involving PEG is included. The ability of PEG to prevent the self-aggregation of liposomes is considered as a possible means by which it extends circulation longevity. Also, a "dysopsonization" phenomenon where PEG actually promotes binding of certain proteins that then mask the vehicle is discussed.